Investigating the knowledge creation processes in a Learning Management System (LMS) - Ahmad, Mazida; Abbas, Merza; Wan Yahaya, Wan Ahmad Jaafar; Abdul Salam, Sobihatun Nur (2012)
SECI model is commonly used in explaining the process of interaction and transaction of tacit and explicit knowledge between the experts and novices.The model involves Socialization, Externalization, Combination, and Internalization process derived from organizational practice. As its applicability in the educational context is inconclusive, an investigation was conducted to see if the model could explain the knowledge creation processes for the expository (high hierarchical structure) teaching method in a set of online courses.This paper reports the findings based on a survey conducted on a sample comprised of 371 students enrolled in LMS-supported courses at a university in Malaysia.The instrument has been developed based on the SECI model to measure the interaction and transaction processes for content-based and content-free skills.The data was collected in stages over a semester and analyzed using the latent variable method in Structural Equation Modeling (SEM).The latent variable method requires the extraction of the factors investigated through a measurement model followed by the construction of the structural model employing the extracted factors.For content-free skills, the measurement model reported a good fit for the data, with all factors having significant direct effects hence follows the complete SECI model.However, the structural model analysis for content-based skills reported an acceptable fit for the data with one insignificant hypothesized direct effect, thus produced an incomplete SECI model.The overall findings demonstrates that SECI model is applicable to educational settings and worked well in situations or contexts where students were already proficient.